New quorum quenching bacteria for controlling biofilm thickness in the membrane aerated biofilm reactor - Taskan, Banu; Taskan, Ergin; Hasar, Halil (Elsevier, 2022)
The uncontrolled increase of biofilm thickness on the membrane surface directly affects substrate diffusion rate, pollutant removal efficiency, and microbial ecology of the membrane aerated biofilm reactor (MABR). This study aimed to control the biofilm growth using a promising antifouling strategy called quorum quenching (QQ). For this purpose, new QQ bacteria (Bacillus methylotrophicus BT1, Klebsiella pneumoniae BT2, Lysinibacillus fusiformis BT3, and Achromobacter xylosoxidans BT4) were isolated and immobilized to control the biofilm thickness on the membrane fibers in MABR. The Bacillus methylotrophicus BT1 with the highest QQ activity disrupted bacterial communication among microorganisms, provided a relatively thin and dense biofilm thickness (250 mu m), and exhibited the best MABR performance. The amount of EPS secreted by the microorganisms significantly decreased due to the increase in the QQ activities of the QQ bacteria. A significant COD removal performance improvement of 74.5% compared to the control-MABR was achieved by MABR containing BT1. Microbial analysis revealed a change in the microbial community structure of biofilms in the MABRs containing different QQ bacteria. In conclusion, the newly isolated QQ bacteria effectively could be controlled biofilm formation on the membrane fibers in MABR systems, and the results obtained can form the basis for larger-scale studies.
Keywords: Membrane aerated biofilm reactor (MABR); Quorum quenching (QQ); Isolation of bacteria; Biofilm thickness; Microbial community